The effect of emotional intelligence on the learning achievement of physics high school students - Tepi, Maria Yosephina; Daud, Maimunah Haji; Nasar, Adrianus; Wolo, Daniel (Univeritas Papua, 2022)
This study aims to assess the impact of emotional intelligence on students' physics learning achievement. Eighty-three students were taken randomly to measure their emotional intelligence. A questionnaire that measured emotional intelligence and learning achievement was obtained through school documentation. The data were analyzed using simple regression. The findings show that empathy is the aspect of emotional intelligence that gets the highest score. The regression results show Fcount (25.87) > Ftable (3.96). The findings of this research reveal that there is an influence of emotional intelligence on students' physics learning achievement. Emotional intelligence is a factor in a student's ability to learn and succeed in physics.